Drug Prescribing Pattern In Upper Respiratory Tract Infection In Children Aged 1 – 14 Years - MEENA K.NANDIMATH; SAM AHUJA (International Journal of Pharma and Bio Sciences, 2012)
The infections of the upper respiratory tract including nose, the para nasal sinuses, adenoids, tonsils, nasopharynx and eustachian tube is the most frequently occurring illness of childhood. Most instances of URTI are of viral origin and resolve spontaneously. Antibiotic treatment is needed only if symptoms persist for 10-14 days. There is a need of rational prescription of medicines to minimize medicinal error in children. The pattern of prescriptions in URTI in children aged 1 to 14 years were analyzed and evaluated for the rationality of drug usage. The data from the outpatient record of each patient was collected in a separate proforma and subjected to descriptive statistical analysis using Microsoft Excel. The study included only one prescription per patient. Utilization of different classes of drugs as well as individual drug was analyzed and presented as percentage. Remedial measures were suggested to avoid erroneous prescriptions.